Metaforyczne kryterium waloryzacji dyrektyw praktycznych - Stańczyk, Piotr (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
This article identifies a trend in the organizational researches which use a metaphor as some way of the valuation of practical directives. Moreover, the problems connected with the valuation of practical directives and possible manners of solving them are described. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (10); 2006; nr 1149, s. 44-50